Unfair contract terms in European law : a study in comparative and EC law - Nebbia, Paolisa (Modern studies in European law, 2007)
Examines Directive 93/13 on Unfair Terms in Consumer Contracts and its implementation with a twofold aim. Showing a broader, more 'European' concern, this book also aims to identify the contours and features of the emerging European legal tradition, and to assess the impact that this may have on the domestic traditions.